Artist's Statement: REBIRTH - Angelica Walton (Interdisciplinary Journal of Partnership Studies)
Artist’s Statement for the cover art of the Interdisciplinary Journal of Partnership Studies, Volume 11, Issue 2: Rebirth. Mixed Media